A pH-driven ring translocation switch against cancer cells. Issue 98 (21st November 2018) - Cheng, Qian; Yin, Hang; Rosas, Roselyne; Gigmes, Didier; Ouari, Olivier; Wang, Ruibing; Kermagoret, Anthony; Bardelang, David
Abstract : A molecular switch built with cucurbit[7]uril and a 3-station viologen-phenylene-imidazole compound has showed pH actuated ring translocation with high fatigue resistance and promising features against cancer cells. Abstract : A molecular switch built with cucurbit[7]uril and a 3-station viologen-phenylene-imidazole compound exhibited pH actuated ring translocation with high fatigue resistance (up to 10 2 cycles). The switch movement was harnessed toward selectively masking the toxicity of the viologen fragment at neutral pH near non-cancerous cells, while exposing it at acid pH near cancer cells.